Representing spatial objects in data warehouses: a logical solution. (5th November 2019) - Garani, Georgia
Spatial data warehouse logical design involves mainly extending the techniques used in relational logical data warehouse design for the support of spatial objects, i.e., geometric objects in space. Spatial objects can have different geometric granularities and can be found at different hierarchical levels of a dimension in the logical model of a data warehouse. This paper addresses data warehouse logical design considerations for a consolidated representation of spatial and non-spatial data. The novelty of the model presented in this paper is the representation of spatial objects in a logical and semantically effective manner. With this approach, complex spatial objects can be modelled in a generic and user-friendly format. The model also includes ROLAP operations supporting the navigation across different dimensions' levels and the execution of queries. The functionality of the model is also provided by a number of example queries.